QUR’ANIC ECONOMIC INTERPRETATION THROUGH A THEMATIC EXEGESIS APPROACH IN DETERMINING THE LEGAL STATUS OF CONTROVERSIAL FEES AND PROFIT MARGINS IN ISLAMIC BANKING ON DIGITAL ECONOMY PLATFORMS - Mukhtar Yunus (Program Pascasarjana UIN Sumatera Utara, 2025)
The development of e-economy platforms in 2025 has brought significant transformation to the Islamic banking industry, particularly regarding the determination of fees and profit margins, which often gives rise to legal controversies. This article analyzes Qur’anic economic interpretation through a thematic exegesis approach to determine the legality of administrative fees, provision fees, and profit margins in digital transactions within Islamic banks. Using the thematic exegesis method (al-tafsīr al-mawḍū‘ī) with an integrative-economic approach, this study examines Qur’anic verses related to muamalah, usury (riba), and transactional justice. The findings show that several fee-setting practices in Islamic banks on e-economy platforms require recontextualization based on maqāṣid al-sharī‘ah, particularly in protecting wealth (ḥifẓ al-māl) and life/welfare (ḥifẓ al-nafs). This study concludes that the legal determination of fees and margins must consider the principles of mutual assistance (ta‘āwun) and justice (‘adl), while avoiding hidden elements of riba, gharar, and ḍarar within digital transaction structures. These findings provide a theological foundation for contemporary fatwas and Financial Services Authority regulations related to Islamic fintech.